HUBUNGAN ANTARA KEPRIBADIAN DENGAN KEJADIAN RELAPS PADA PASIEN KANKER PAYUDARA DI POLI ONKOLOGI RSUD DR. SOETOMO SURABAYA - Adiwibawa, Danang Nur (Fakultas Kedokteran Universitas Islam Al-Azhar, 2020)
Background. Breast cancer is a major health problem that affects the lives of millions of women. Some patients have treatment but still found relapse.Suggest personality factors influence relapse breast cancer.But until now it is still controversy. Methods. Analytic research observational case control study to find relationship between personality with the incidence of relapse in breast cancer patients and comparing personality relapse and non relapse. Research in Poli Onkologi RSUD Dr.Soetomo with 56 patients,28 patients relapse and 28 non relapse.Use Instrument OCEAN-Big Five Inventory 44 Quessioner and Demogarfi Quessioner. Result. There is no relationship between personality with incidence of relapse (p>0,05). neuroticism personality (29%) in relapse, openness personality (32%) and extraversion personality (36%) in non relapse. Conclusion. The incidence of relapse breast cancer is not simply due to personality but maybe other factors.